Phase Sequence Online Correction Based on PIC Technique - Bilal A. Mubdir; Dara H. Amin (International Journal of Advances in Applied Sciences, 2017)
Monitoring the delivered power quality (PQ) to a critical load, is a worry issue since it is matter as much as critical or quality sensitive equipment connected to the electrical network. Various PQ problems such as noise, voltage imbalance, waveform distortion, phase imbalance, phase sequence, over voltage or sag are the most popular quality problems that could be detected and fixed if needed. The present work presents a design and practical implementation of electronic embedded system to monitoring the sequence of a three phase electrical system and detects the occurrence of any change in the sequence and fixes it online, correct the phase sequence immediately during less than 70 milli-seconds. PIC Microchip microcontroller has been used as the core of the present system, where the correction of the phases has been achieved by using traditional electromechanical relays. The system has been tested successfully and it functions properly even with multiple sequence changes.